2016
DOI: 10.2298/vsp141208025p
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine poisoning in elderly

Abstract: Background/Aim. Benzodiazepines are among the most frequently ingested drugs in self-poisonings. Elderly may be at greater risk compared with younger individuals due to impaired metabolism and increased sensitivity to benzodiazepines. The aim of this study was to assess toxicity of benzodiazepines in elderly attempted suicide. Methods. A retrospective study of consecutive presentations to hospital after self-poisoning with benzodiazepines was done. Collected data consisted of patient's cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Currently, more attention is paid to complementary and alternative medicine (CAM) strategies, because they have fewer complications and are easy to access (Mohammadpour et al, 2014). These strategies are highly recommended in older patients with an impaired metabolism and increased sensitivity to the side effects of drugs (Perković-Vukčević, Vuković-Ercegović, Šegrt, Đorđević, & Jović-Stošić, 2016). For instance, cognitive and cardiovascular adverse effects among older people, after the use of tranquillisers and cardiovascular drugs, are very common (Sztramko, Chau, & Wong, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more attention is paid to complementary and alternative medicine (CAM) strategies, because they have fewer complications and are easy to access (Mohammadpour et al, 2014). These strategies are highly recommended in older patients with an impaired metabolism and increased sensitivity to the side effects of drugs (Perković-Vukčević, Vuković-Ercegović, Šegrt, Đorđević, & Jović-Stošić, 2016). For instance, cognitive and cardiovascular adverse effects among older people, after the use of tranquillisers and cardiovascular drugs, are very common (Sztramko, Chau, & Wong, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Benzodiazepines potentiate the respiratory effects of opioids and are associated with aberrant drug‐taking behaviors . Elderly patients are at heightened risk of adverse incidence of overdose and other injuries (such as fractures and falls) from both opioids and benzodiazepines . Substantial nonmedical use of prescription drugs, especially opioids and sedatives, has been documented among elderly Americans, most worryingly with suicidal intent …”
Section: Discussionmentioning
confidence: 99%
“…Robustness tests not shown here confirm that these results are substantively unchanged through other model specifications, such as ordi- from both opioids and benzodiazepines. [30][31][32] Substantial nonmedical use of prescription drugs, especially opioids and sedatives, has been documented among elderly Americans, most worryingly with suicidal intent. 33,34 While these results pile on to the substantial clinical literature documenting the harmful interaction between these classes of drugs, they also reveal an ecological risk to high levels of benzodiazepine prescriptions, especially alongside elevated rates of opioid prescriptions, that has not yet been documented in the literature.…”
Section: Robustness Testsmentioning
confidence: 99%
“…In addition, significant increases in the prevalence of BZ exposure and overdose have been observed, especially in children [13]. In other reports, acute BZ intoxication and accidental overdose have been reported in elderly people [14][15][16]. Furthermore, some studies have reported that antidepressants are more commonly used for intentional drug overdose in women than in men [17][18][19].…”
Section: Introductionmentioning
confidence: 99%